Aquaglyceroporin-7 ameliorates sorafenib resistance and immune evasion in hepatocellular carcinoma through inhibition of lipid accumulation - Guangsi He; Wenzhu Shao; Weifei Wang; Lu Sun; Beibei Gao; Jie Wei (Cellular and Molecular Life Sciences)
Abstract Sorafenib, a multikinase inhibitor targeting cell growth and angiogenesis, was approved for advanced unresectable hepatocellular carcinoma (HCC) in 2007. This investigation aims to elucidate the involvement of aquaglyceroporin-7 (AQP7) in regulating sorafenib resistance (SR) in HCC. AQP7 was downregulated in HCC-SR cells. AQP7 upregulation inhibited lipid accumulation, enhanced the sorafenib sensitivity of SR cells, and improved immune evasion. TBX19 protein was elevated in HCC-SR cells, and TBX19 repressed AQP7 transcription by binding to its promoter. E3-ubiquitin ligase MGRN1 was reduced in HCC, and its overexpression promoted TBX19 degradation. MGRN1 overexpression enhanced AQP7 and improved SR and immune evasion in HCC, which was reversed by TBX19 overexpression. Mouse HCC cells Hepa1-6 were used to construct an orthotopic tumor model and to analyze the effects of AQP7 and MGRN1 expression on the in vivo antitumor effects of Sorafenib, lipid accumulation in tumor tissues, and immune cell infiltration. MGRN1 silencing in Hepa1-6 cells induced sorafenib resistance and created an immunosuppressive tumor microenvironment, which was repressed by AQP7 upregulation. In conclusion, MGRN1 loss in HCC-SR cells blocked TBX19 degradation and strengthened TBX19-mediated AQP7 repression, leading to immune evasion. Targeting this signaling might offer a promising therapeutic strategy to overcome SR in HCC.